You are on page 1of 2

The Arithmetic-Geometric Mean Inequality

Jack Haviland

Here we will compare the arithmetic and geometric means and see that the arithmetic is always greater
than or equal to the geometric. This will require a somewhat complicated proof, beginning with this lemma.

Lemma. For all lists of real numbers of length 2n for some n a1 , a2 , . . . , an ,

a1 + a2 + . . . + a2n √
n
n
≥ 2 a1 a2 · · · a2n
2
Proof. We argue by induction on n. We consider the base case n = 1 because it is useful in multiple ways,
but the case n = 0 is obviously true as well.
Base case: The square of any real number is greater than zero. So (a1 − a2 )2 ≥ 0. With some algebra, we
see:

(a1 − a2 )2 ≥ 0
a21 − 2a1 a2 + a22 ≥ 0
a21 + 2a1 a2 + a22 ≥ 4a1 a2
(a1 + a2 )2
≥ a1 a2
4
a1 + a2 √
≥ a1 a2
2
The motivation for this process comes from working backwards from the final statement, but it is cleaner to
show this way. We now see that the base case holds, so on to the inductive step.
Suppose that
a1 + a2 + . . . + a2n √
n
≥ 2 a1 a2 · · · a2n
2n
A list of length 2n+1 can be split into two lists of length 2n : a1 , a2 , . . . , a2n and a2n −1 , a2n +1 , . . . , a2n+1 .
Now let S1 denote the sum of the terms of the first sequence and S2 the second. S1 and S2 are both real
numbers. From the base case, we know that
S1 + S2 p
≥ S1 · S2
2
By inductive hypothesis, we also know that
S1 √
n S2 √
≥ 2 a1 a2 · · · a2n and ≥ 2n a2n +1 a2n +2 · · · a2n+1
2n 2n
Therefore,
S1 · S2 √
n √
n n
≥ 2 a1 a2 · · · a2n · 2n a2n +1 a2n +2 · · · a2n+1
r2 · 2 q √
S1 · S2 2n
√ √
2n+1
n+1
≥ a1 a2 · · · a2n · 2n a2n +1 a2n +2 · · · a2n+1 = a1 a2 · · · a2n+1
2

1
Finally, we have
r
a1 + a2 + . . . + a2n+1 S1 + S2 p S1 · S2 √
2n+1
n+1
= n+1
≥ S1 · S2 ≥ ≥ a1 a2 · · · a2n+1
2 2 2n+1
Thus our induction is completed and our lemma is proven true.
Theorem. For all lists of real numbers a1 , a2 , . . . , an ,
a1 + a2 + . . . + an √
≥ n a1 a2 · · · an
n
Proof. Suppose for contradiction that for some list of real numbers as above, the inequality did not hold. In
other words,
a1 + a2 + . . . + an √
< n a1 a2 · · · an
n
Now we can add another term to this list, call it an+1 , and let it be equal to the arithmetic mean of the
previous terms. Then
n · an+1 = a1 + a2 + . . . + an
Taking the arithmetic mean of this new list, we have
 
a1 + a2 + . . . + an+1 (n · an+1 ) + an+1 n+1
= = (an+1 ) = an+1
n+1 n+1 n+1

So the arithmetic mean of our new list is the same as the old one. Now, we also know that

an+1 < n a1 a2 · · · an ⇒ (an+1 )n < a1 a2 · · · an

(an+1 )n+1 < a1 a2 · · · an an+1

an+1 < n+1 a1 a2 · · · an+1
a1 + a2 + . . . + an+1 √
< n+1 a1 a2 · · · an+1
n+1
This procedure can be carried out for a list of any length, so if there is any list such where this is true, it is
not true for all longer lists as well. However, for any length n there exists a longer list of length 2n . From
our lemma, we know that the arithmetic-geometric mean inequality holds for any list of length 2n . A list of
any length would contradict this, so there cannot be a list of any length for which the arithmetic-geometric
inequality does not hold.